Implementation of the emergency severity index in the emergency department: A staff attitude survey from three perspectives Einführung des emergency-severity-index in der zentralen notaufnahme akzeptanzstudie aus drei perspektiven - Schüler, S.; Eisenbarth, H.; Fersterra, A.; Schob, M.; Dormann, H. (Notfall und Rettungsmedizin, 2013)
Background. Triage in the emergency department is a necessary tool in order to briefly evaluate and prioritize the acuity of patient symptoms. Despite the reliability and validity of this triage tool in the literature, a successful reorganization of the admission process by implementing the emergency severity index (ESI) could only be reached by the positive perception and acceptance of this tool in the daily routine. Therefore a staff attitude survey was conducted. Methods. After implementation of the triage tool, the entire professional staff was interviewed by a standardized questionnaire 6 months later. In the emergency department of the Fürth Clinic a tertiary care level III hospital, questions to the emergency service (R), the nursing staff (P) and the physicians (Ä) before and after ESI implementation and about the training program were evaluated and categorized in the following categories: 0 not true, 1 sometimes true, 2 generally true, 3 always true. Mean values were considered (X̄). Results. Prior to the implementation of ESI most patients were treated according to the waiting time (XÄ 1.9; X̄P 2.0; X̄R 2.3), which led to a perceived dissatisfaction of waiting patients (X̄P 2.1). The reorganization by implementing the triage tool was rated positively across all professions (X̄Ä 2.2; X̄P 2.7; X̄R 2.5), as the interprofessional collaboration and perceptions of actual improvement in emergency service function, effect on own job and effect on patient care were all positively rated (X̄Ä 1.9; X̄P 2.2; XR 2.1). Waiting patients were perceived to feel and act in a more satisfied manner (XP 2.2). The triage training concept was considered from the triage nursing point of view as reasonable, necessary and effective (X̄P 2.7). Both emergency services staff and physicians indicated a general acceptance of the triage tool (X̄R 2.2; X̄Ä 2.3) but felt that the individual expertise was not restricted (X̄Ä 0.3; X R 0.7). Conclusions. All professions agreed the need for triage and the positive indications and effectiveness in optimizing the admissions process in the emergency department. By the stepwise introduction and training concept of ESI a positive perception and acceptance of the triage tool could be achieved. © Springer-Verlag 2013.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Acceptance; Emergency department; Emergency serverity index; Rescue service; Triage